2006
DOI: 10.1111/j.1525-1438.2006.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

HER-2 codon 655 polymorphism in cervical carcinogenesis

Abstract: HER-2 codon 655 polymorphism together with human papillomavirus (HPV) types were examined in a total of 279 cervical smear samples. Forty-nine patients with high-grade squamous intraepithelial lesion had higher frequency of high-risk HPV than 167 patients with low-grade squamous intraepithelial lesion and 63 controls. There was no statistical difference in the frequencies of HER-2 Ile/Ile, Ile/Val, and Val/Val genotypes between squamous intraepithelial lesions (SILs) and controls. When the Ile/Ile genotype was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…Although the function of HER2 exonic polymorphism is clear, the association between HER2 SNP rs1136201 and CCa is still controversial 28,29. Our results show that rs1136201 alone does not significantly influence the risk of CCa, which coincide to the previous report in a Japanese population 28; however our results do not align with the population in Poland 29. Such difference might be due to the distinction of Asian and Caucasian populations.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Although the function of HER2 exonic polymorphism is clear, the association between HER2 SNP rs1136201 and CCa is still controversial 28,29. Our results show that rs1136201 alone does not significantly influence the risk of CCa, which coincide to the previous report in a Japanese population 28; however our results do not align with the population in Poland 29. Such difference might be due to the distinction of Asian and Caucasian populations.…”
Section: Discussioncontrasting
confidence: 66%
“…Variant of rs1136201 might lead to destabilization of the active HER2 heterodimers, consequently increases signal transduction for HER2 expression, and finally stimulates kinase activity and malignant transformation 26, 27. Although the function of HER2 exonic polymorphism is clear, the association between HER2 SNP rs1136201 and CCa is still controversial 28,29. Our results show that rs1136201 alone does not significantly influence the risk of CCa, which coincide to the previous report in a Japanese population 28; however our results do not align with the population in Poland 29.…”
Section: Discussionmentioning
confidence: 99%
“…Both mNeuNT and the human ErbB2 codon 655 polymorphism are single amino acid changes within the transmembrane domain of ErbB2 [47]–[49] suggesting that the transmembrane domain mediates critical interactions in disease. Interestingly, low grade in situ lesions of the cervix are not associated with this polymorphism [50] while advanced cervical cancer is strongly associated with it [51]. In head and neck squamous cell carcinoma, codon 655 polymorphism is associated with malignancy [52].…”
Section: Discussionmentioning
confidence: 99%
“…34 These data suggest the possibility that the HER2 +655 A/G polymorphism might contribute to the disease susceptibility of these cancers. However, Ueda et al 36 36 Wang et al, 35 and McKay et al 38 Fleishman et al 41 suggested that the HER2 +655 A/G polymorphism was possibly associated with the structural and functional alteration of the HER2 protein since it is located in the transmembrance coding region. 42 Interestingly, the activation of HER2 was thought to be correlated with the hormone refractory state of endometrial cancer.…”
Section: Discussionmentioning
confidence: 96%
“…34 These data suggest the possibility that the HER2 +655 A/G polymorphism might contribute to the disease susceptibility of these cancers. However, Ueda et al 36 demonstrated that this polymorphism was not associated with the onset of uterine cervical cancer in a Japanese population. Wang et al 35 failed to show an association between bladder cancer and this polymorphism in a Japanese population.…”
Section: Discussionmentioning
confidence: 98%